A molecular dynamics study into zeolitic imidazolate frameworks-based capacitive deionization electrodes for Mg²⁺ removal and seawater desalination - Hong, Terence Zhi Xiang (2022)
In this study, molecular dynamics simulations are performed to study the surface interactions between the zeolitic imidazolate frameworks (ZIFs)-based capacitive deionization (CDI) electrodes with seawater and Mg2+ ions. Using the same organic linkers but different metal atoms to construct the electrodes, the CDI performance of the said electrodes is tested in terms of ion rejection and water flux. The effects of metal atoms on the ZIF interactions with the seawater and Mg2+ are studied and explained using ion distribution, water velocity, and radial distribution function (RDF). The results revealed that the metal and N atoms have a strong affinity for ions, and the maximum ion rejection by the electrode achieved in the presence of Mg2+ is 97.6%. Furthermore, ZIF hydrophilicity is dependent on the metal atoms which have the strongest affinity with water molecules, and this water affinity determines the water flux. Overall, the results proved that metal atoms can influence the ZIF performance. Among the four ZIFs tested, CdIF-1 has the best performance.